Evaluating supplier performance using data envelopment analysis (DEA) - Siti Sarah, Yahya (2015)
Data Envelopment Analysis (DEA) has been widely applied to address various decision analysis problems due to its usefulness in evaluating multi-criterion systems and providing improvement targets for such systems. A supplier selection is inherently a multi-criterion decision problem, and DEA has been applied to evaluate suppliers. This paper proposes and demonstrates the application of DEA in evaluating the overall performances of suppliers in a firm. A research is then presented to demonstrate supplier performance evaluation using DEA for supplier selection and consideration of performance improvement. In this research, supplier performance was measured in terms of efficiency and performance. Out of 8 suppliers of Usahawan.com Sdn Bhd was analyzed, DEA identified 2 efficient suppliers. The rest 6 suppliers’ slack factors that contribute to inefficiency were point out. Some variable have rooms to be improving in order to achieve great performance. The most efficient supplier is used as reference set to which are not efficient. Criteria that was used for supplier performance measurement in this study used for DEA application (distance, late deliveries, supply variety, quality) is consistent with academic research results on most important supplier evaluation criteria (Dickson, 2000) and most often used criteria for supplier evaluation in academic research (Weber, 2004).